FORMATION OF PROFESSIONAL COMPETENCE OF MASTERS OF PRESCHOOL EDUCATION: A GUIDE TO THE MODERN - Bielienka, Hanna; Polovina, Olena; Kondratets, Inna; Shynkar, Tetiana (Educological discourse, 2021)
The article considers the issue of professional training of future preschool teachers. The example of a new training course for the specialty 012 Preschool education "Art Education of Preschool Children" presents opportunities to improve the quality of education and the formation of information culture of applicants for the second (master's) level of training by the means of information and communication technologies. The current state of the problem is analyzed and the contradictions in the process of teaching professional methods between the existing theoretical basis of professional training of future teachers and the insufficient level of professional competence of graduates, which is partly explained by the low level of motivation of many students to work in preschool education. The scientific research devoted to the application of information and communication technologies in the educational process, the definition of levels of readiness of students to use information and communication technologies and skills of the teacher who has mastered information and communication competence are analyzed. The article presents the results of a study of the levels of formation of artistic competence of undergraduates by motivational, emotional, intellectual, activity criteria and relevant indicators; methods of pedagogical diagnostics are specified. The principles, methods, and forms of using information and communication technologies in the context of the discipline "Art Education of Preschool Children" are revealed. The correlation between forms and methods of interaction of the teacher with pupils based on the use of information and communication technologies is shown. Factors of efficiency of use of information and communication technologies are defined: increase of interest of students to academic discipline, motivation to self-improvement and self-development, modernization of content of educational disciplines by innovative forms of interaction, methods, and receptions of formation of corresponding professional competence at future masters.